Exploring the Immunomodulatory Moonlighting Activities of Acute Phase Proteins for Tolerogenic Dendritic Cell Generation - Serrano, Inmaculada; Luque, Ana; Aran, Josep M. (Frontiers in Immunology, 2018)
The acute phase response is generated by an overwhelming immune-inflammatory process against infection or tissue damage, and represents the initial response of the organism in an attempt to return to homeostasis. It is mediated by acute phase proteins (APPs), an assortment of highly conserved plasma reactants of seemingly different functions that, however, share a common protective role from injury. Recent studies have suggested a crosstalk between several APPs and the mononuclear phagocyte system (MPS) in the resolution of inflammation, to restore tissue integrity and function. In fact, monocyte-derived dendritic cells (Mo-DCs), an integral component of the MPS, play a fundamental role both in the regulation of antigen-specific adaptive responses and in the development of immunologic memory and tolerance, particularly in inflammatory settings. Due to their high plasticity, Mo-DCs can be modeled in vitro towards a tolerogenic phenotype for the treatment of aberrant immune-inflammatory conditions such as autoimmune diseases and allotransplantation, with the phenotypic outcome of these cells depending on the immunomodulatory agent employed. Yet, recent immunotherapy trials have emphasized the drawbacks and challenges facing tolerogenic Mo-DC generation for clinical use, such as reduced therapeutic efficacy and limited in vivo stability of the tolerogenic activity. In this review, we will underline the potential relevance and advantages of APPs for tolerogenic DC production with respect to currently employed immunomodulatory/immunosuppressant compounds. A further understanding of the mechanisms of action underlying the moonlighting immunomodulatory activities exhibited by several APPs over DCs could lead to more efficacious, safe and stable protocols for precision tolerogenic immunotherapy.